Loss of Beaches due to Anthropic Action and Geodynamic Phenomena: Miraflores - La Chira (Costa Verde), Lima-Peru - San Román Moscoso, Carmen Gladys (2023)
The objective of the research was to describe the current problems generated by anthropic action and geodynamic phenomena causing the loss of sandy beaches in the Miraflores - La Chira (Costa Verde) stretch, Lima. Methodologically, the study consisted of the elaboration of the geodynamic map and cross sections at a scale of 1/5000, aimed at the diagnosis of geological risks together with the sedimentological analysis, focused on understanding the general aspects of the dynamics of erosion, transport, deposition and the associated human effect. Likewise, in order to estimate the modification of the beach profile and the most vulnerable areas, aerial photos from 1960 were compared with recent ones. Finally, through the interpretation of the vulnerability index, a valuation of 0.38 and 15.12 was obtained, which corresponds to the moderate level category in both beaches. It is concluded that the role of humans is preponderant in the alteration of the geoforms.